2019
DOI: 10.1002/jctb.6192
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of μ‐stat methanol feeding control in fed‐batch fermentation of Pichia pastoris producing HBsAg: an open‐loop control versus recurrent artificial neural network‐based feedback control

Abstract: BACKGROUND In recent decades, artificial neural network (ANN) has been shown to be a robust and promising tool in monitoring and controlling bioprocess systems. In a previous study, the authors designed a highly accurate and precise recurrent neural network (RNN) for predicting the biomass amount of recombinant Pichia pastoris Mut+ producing intracellular hepatitis B surface antigen (HBsAg) during fed‐batch methanol fermentation. In the current work, the aim was to compare the production efficiency of HBsAg be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…Recurrent neural network (RNN) is an artificial neural network for series data, which can transfer information between neurons and express the correlation between data while taking the time dimension into account. RNNs have been widely used in the time-series prediction of key state variables and diagnosing faults in fermentation, particularly in industrial-scale production [ 89 , 90 ]. Beiroti et al accurately predicted the biomass of recombinant Pichia pastoris Mut + , and optimized the process conditions in the methanol induction phase of the fed-batch fermentation [ 91 ].…”
Section: Development Of Modelingmentioning
confidence: 99%
“…Recurrent neural network (RNN) is an artificial neural network for series data, which can transfer information between neurons and express the correlation between data while taking the time dimension into account. RNNs have been widely used in the time-series prediction of key state variables and diagnosing faults in fermentation, particularly in industrial-scale production [ 89 , 90 ]. Beiroti et al accurately predicted the biomass of recombinant Pichia pastoris Mut + , and optimized the process conditions in the methanol induction phase of the fed-batch fermentation [ 91 ].…”
Section: Development Of Modelingmentioning
confidence: 99%
“…The authors reported that the newly developed RNN was used in a PID control system for maintaining a predefined specific growth rate at a constant value by adjusting the methanol feed rate. They report that the RNN based feedback controller has a “significantly higher process efficiency” than a conventional open-loop controller with predefined feeding strategy [104] .…”
Section: Modeling In Process Controlmentioning
confidence: 99%
“…Despite this limitation, ANNs have demonstrated success in predicting the behavior of diverse fermentation systems, prompting their utilization in bioprocess control applications. Recent applications of ANN models in cell biomass estimation, encompass regulating specific growth rate [30], optimizing cell biomass [31][32][33], and estimating [33,34] or tracking a predefined substrate concentration trajectory [35].…”
Section: Introductionmentioning
confidence: 99%